Role of Microencapsulated Essential Oil and Pepper Resin in the Diet of Cows in the Third Lactation Phase on Immunological Pathways - Karoline Wagner Leal; Marta Lizandra do Rego Leal; Gabriel S. Klein; Andrei Lucas R. Brunetto; Guilherme Luiz Deolindo; Camila Eduarda Justen; Matheus Dellaméa Baldissera; Tainara L. Santos; Daniela Zanini; Rafael C. de Araujo; Aleksandro Schafer da Silva (Veterinary Sciences)
The objective was to determine whether dairy cows may activate traditional and alternative inflammatory pathways by consuming a combination of a phytogenic diet (essential oil and pepper resin). Twenty pregnant Jersey cows in the final (third) lactation phase (260 days in milk) were divided into two groups: control, with no additive consumption, and test, with the addition of the phytogenic to the concentrate portion of the diet (150 mg/day/kg dry matter). Blood samples were collected on experimental days 1, 7, 14, 21, 28, 35, and 42 by coccygeal vein puncture to assess the complete blood count, serum biochemistry of levels of total protein, albumin, and globulin, as well as carbohydrate metabolism (glucose), lipid metabolism (cholesterol and triglycerides), protein metabolism (urea), activities of hepatic enzymes (gamma-glutamyl transferase (GGT) and aspartate aminotransferase (AST)), cytokine levels (interleukins IL-1β, IL-6, and IL-10), antioxidant response [thiobarbituric acid reactive substances (TBARS), reactive oxygen species (ROS), total thiol (PSH), and non-protein thiol (NPSH), and glutathione S(GST)], cholinergic system [total cholinesterase (ChE) and acetylcholinesterase (AChE)], purinergic signaling [NTPDase, 5′ectonucleotidase and adenosine deaminase (ADA)], and energetic metabolism enzymes [creatine kinase (CK), pyruvate kinase (PK), and adenylate kinase (AK)]. Productive performance was assessed through feed intake and milk production. The results revealed that the use of phytogenic compounds significantly influenced the cholinergic system and purinergic signaling associated with immunology. The reduction in cholinesterase (ChE) activity and the increase in acetylcholinesterase (AChE) activity in lymphocytes suggest the modulation of the cholinergic system, enhancing the immune response. Furthermore, the elevated activity of adenosine deaminase (ADA) in lymphocytes and platelets, together with increased ATP and ADP hydrolysis in platelets, indicates the beneficial regulation of purinergic signaling, potentially contributing to inflammatory modulation. These effects were accompanied by a lower production of pro-inflammatory cytokines (IL-1β and IL-6) and a higher production of IL-10, reinforcing an anti-inflammatory profile. The reduced leukocyte and lymphocyte counts may reflect a lower inflammatory demand, while the increased levels of NPSH and GST antioxidants suggest cellular protection. Despite these physiological changes, productive performance and milk quality remained unaffected. In summary and practical terms, including this additive in the cows’ diet benefits the cow’s health in the final third of gestation when the animal already has a reduced immune response due to advanced gestation.